Apparent contradictions in the Qur’an: preconditions, causes, and scholarly methodologies of resolution - Elatrash, Radwan Jamal Yousef; Osmani, Noor Mohammad; Mohiuddin, Mohammad (IIUM Press, 2025)
This study investigates the phenomenon of apparent contradictions in the Qur’an by examining the conditions under which such perceptions arise, the causes that contribute to them, and the scholarly methods employed for resolution. The central issue addressed is the misinterpretation of verses that appear conflicting, despite the Qur’an’s divine origin and inherent coherence. Using inductive and analytical approaches, the research engages with classical uṣ ūlīprinciples to clarify the preconditions for a genuine contradiction and demonstrates that these conditions are never realized in the Qur’an. It further analyzes common sources of perceived conflict, including generality versus specificity, absoluteness versus qualification, abrogation, and contextual variation. The study highlights the interpretive strategies of scholars, emphasizing the importance of linguistic precision, contextual analysis, and the uṣ ūlīframework in safeguarding textual integrity. The findings affirm that true contradiction in the Qur’an is impossible, and that apparent conflicts can be resolved through sound interpretive tools. The research also recommends incorporating these methodologies into Qur’anic and legal studies curricula to enhance critical skills and deepen engagement with the sacred text. Ultimately, it reaffirms the Qur’an’s internal harmony and strengthens intellectual confidence in the Islamic tradition.